Identifying Code Mixing on Instagram: The Case of Chinese-Indonesians - Lubis, Rafi Muhammad; Nazreensyah, Fabian Putra; Siahaan, Daniel Fernando; Anargya, Hafwen; Rangkuti, Rahmadsyah (Jambura Journal of English Teaching and Literature, 2025)
This study looks into code mixing in Chinese-Indonesian users' Instagram descriptions and comments. The research employs a qualitative descriptive approach to identify and categorize the types of code mixing found in online discourse, using Muysken's (2000) typology of code mixing as the analytical framework. Data were carefully gathered from 100 Chinese-Indonesian Instagram caption pages and 40 instagram posts consist of public Instagram accounts of Chinese-Indonesian people, with an emphasis on comments and captions that included multilingual content. Three forms of code mixing are identified by the analysis: congruent lexicalization, alternation, and insertion. The most common type was insertion, with 58 instances, followed by alternation with 30 instances and congruent lexicalization with 12. The results demonstrate the ongoing role of social media in maintaining linguistic diversity by indicating that Instagram functions as a platform for the active performance and maintenance of multilingual practices.